Test-oriented Resilient Requirements Engineering (ToRRE): extending model-based effect chain analysis to verification objectives - Gräßler, Iris; Ebel, Marcel (Proceedings of the Design Society)
Verification and Validation (V&V) are essential processes in engineering Cyber-Physical Systems. However, the role of V&V engineers is often not given sufficient attention. Based on a systematic literature analysis and practical observations, a four-step method for Test-oriented Resilient Requirements Engineering (ToRRE) is developed. The steps are planning V&V, executing V&V activities, documenting V&V activities and analyzing results of V&V activities. Applying ToRRE ensures continuous information flow and traceability. Engineers are enabled to analyze requirements using engineering artifacts connected through Model-Based Systems Engineering. Adopting methods for Model-Based Effect Chain analysis to evaluated test cases and test scenarios, conclusions on requirements engineering and change management are enabled. The method is evaluated in an EU research project.
Keywords: systems engineering (SE); product modelling/models; design methods; verification & validation; test cases & test scenarios